Spectrum of nontraumatic perforation peritonitis: a prospective study of 277 cases with special reference to morbidity and mortality - Garg, Rishi Kumar; Gupta, Rachna; Kailasia, Yogesh; Chhari, Akash Singh; Jain, Mayank; Dubey, Chandrashrekhar (International Surgery Journal, 2016)
Background:Gastrointestinal perforation constitutes one of the most common causes of surgical emergency. The main objective was to study different causes of perforation peritonitis and there sign, symptom. Factors affecting morbidity and mortality. Methods: It was prospective 1 year study conducted in surgical ward of Department of surgery SGMH Rewa (M.P.) during the period August 2014-July 2015.A total of 277 cases of gastrointestinal perforation peritonitis were studied. Patients are selected on the basis of symptom, sign at the time of admission and operative finding. All patients have been studied and results are compared with previous similar studies. Results:Abdominal pain was present in all cases of perforation peritonitis. 89.9% of patient had distension of abdomen, 79.9% complained of fever and 34.3% with vomiting. On per abdominal examination tenderness and distension was present in all cases of perforation. 96.5% of cases had guarding/rigidity. 82.7% of cases had gas under the diaphragm with majority of them in peptic ulcer perforation and minimum in appendicular perforation. Conclusions:Patient with higher age group had higher mortality compare to younger age group. Mortality was maximum 32% in age group of >60 years. Overall mortality in our study was 12.63% and was due to delayed presentation to hospital, delayed operative intervention due to shock and septicaemia, with co-morbidity being the additive factors.